PENGARUH PERSEPSI HARGA, IKLAN, DAN BRAND IMAGE TERHADAP MINAT BELI PADA PRODUK SMARTPHONE SAMSUNG: Studi Pada Mahasiswa FEB UPN Veteran Jakarta - Ahmad Agung Wibisono, - (2019)
This research is a quantitative research that aims to determine the influence of price perception, advertisement and brand image on purchase intention samsung smartphone product. The population in this study was the students of economic and business faculties of UPN veteran Jakarta. The sample size was taken 80 respondents, with nonprobability sampling method, especially purposive sampling. Data collection was done through questionnaires. Analytical technique used is the method of analysis PLS (Partial Least Square). The results of this study indicate that (1) price perception has a significant influence on purchase intention with coefficient value of 0,014. (2) advertisement has no effect significant on purchase intention with coefficient value of 0,107. (3) brand image has a significant influence on purchase intention with coefficient value of 0,000.